The association between oral health literacy and oral health-related behaviours among female adolescents in the Kingdom of Saudi Arabia: A cross-sectional study - Muneera Alzeer; AlBandary AlJameel; Kasper Rosing; Esben Øzhayat (Saudi Dental Journal)
Objectives: Oral health literacy (OHL) is suggested as an important denominator of oral health. This study aimed to identify ways to improve oral health by exploring the association between oral health literacy and oral health-related behaviours among female adolescents in the Eastern Province of the Kingdom of Saudi Arabia (KSA). Methods: This cross-sectional study assessed OHL among 1,889 10th grade female students in the Eastern Province of the KSA. OHL was assessed using an Arabic version of the short version of the Health Literacy in Dentistry scale (A-HeLD-14). Self-reported socio-demographic information and oral health-related behaviours (toothbrushing, dental attendance, and sugary diet consumption) were also collected. The relationship between OHL and oral health-related behaviours was investigated using binary logistic regression, adjusted for socio-demographic information. Results: The binary logistic regression analyses showed that poor OHL was significantly associated with infrequent toothbrushing (p < 0.001) and irregular dental attendance (p = 0.005) but not with consumption of sugary diets. All A-HeLD-14 domains were significantly associated with infrequent toothbrushing, and the domains concerning access, receptivity, and financial barriers were significantly associated with irregular dental attendance. The highest odds ratios (ORs) for infrequent toothbrushing were found in the domains of receptivity (OR = 4.19) and understanding (OR = 3.85) and for irregular dental attendance in the financial barriers (OR = 1.61) and access (OR = 1.49) domains, followed by the receptivity domain (OR = 1.35). Conclusion: Poor OHL was significantly associated with infrequent toothbrushing and irregular dental attendance. Interventions focusing on OHL are warranted to improve oral health-related behaviours and thereby oral health in the population. The aspects that seem most vital to target are improved access to dental care, including the reduction of economic barriers, as well as increased awareness of oral health in the population.